Cognitive load in working memory on trigonometry Learning - Basir, Mochamad Abdul; Maharanib, Hevy Risqi (Department of Mathematics, Universitas Negeri Semarang, 2018)
The cognitive process involves three elements in the human memory system; sensory, working, and long term memory. Unless the long term memory does not have enough preliminary knowledge, the working memory will have difficulties in providing meaning and constructing information as a knowledge, so the working memory is overloaded to understand the problems.With regard to that symptom, the aim of this study is to find out the cognitive load in trigonometric learning. The subjects of this study are students of grade X4 SMAN 6 Semarang. The cognitive load in working memory is caused by three sources, including Intrinsic Cognitive Load (ICL), Extraneous Cognitive Load (ECL), and Germane Cognitive Load (GCL). The results show that ICL can not be manipulated, but ICL can be well processed. Then, ECL can be minimized by material presentation techniques through the help of materials that utilize information technology media. While GCL can be improved through problem solving in developing students' mathematical creative thinking skills.